The Effect of QRIS Convenience and Consumer Trust on Repurchase Intention: Evidence from La Madre Café, Tulang Bawang Barat - Khalifatulloh, Dwiky Fahriza; Rinova, Dora (Institute Of Advanced Knowledge and Science, 2025)
The rapid development of digital payment systems in Indonesia, particularly the use of QRIS, has transformed consumer purchasing behavior. However, consumer trust remains a crucial factor influencing loyalty and repeat purchase.This study aims to analyze the effect of cashless payment convenience and consumer trust on repurchase intention at La Madre Café, Tulang Bawang Barat.The research employed a quantitative approach with a sample of 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression to test the influence of independent variables on repurchase intention.The findings indicate that both cashless payment convenience and consumer trust significantly and positively affect repurchase intention. These results confirm the initial hypothesis that ease of QRIS use and consumer trust are important drivers of repeat purchase decisions. It can be concluded that businesses such as La Madre Café should continue to optimize user-friendly cashless payment systems and strengthen consumer trust through quality service and secure transactions. Future research may explore additional variables such as customer satisfaction, digital literacy, or social media influence, and extend the model to different industries or wider regions for broader insights into consumer behavior in the digital economy.